DASAR PERTIMBANGAN MAJELIS HAKIM DALAM MEMUTUS PERKARA TINDAK PIDANA MELAKUKAN USAHA PENAMBANGAN TANPA IZIN USAHA (STUDI KASUS PUTUSAN NOMOR 30/PID.B/LH/2019/PN PTI) - Desy Komaria; Arrum Budi Leksono (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
As stated in the relevant law, Mining is part or all of the stages of activity in the context of research, management and exploitation of minerals or coal which includes general investigations, exploration, feasibility studies, construction, mining, processing and/or refining, or development and / or utilization, transportation and sale, as well as post-mining activities. The research method used is a normative research method that focuses on library research to obtain secondary data from legal materials. The normative approach is carried out by reviewing the applicable provisions or laws and regulations. The results of the study show that the basis for the consideration of the panel of judges in deciding the case number Decision Number 30/Pid.B/LH/2019/PN Pti is based on the legal facts that were revealed at trial in the form of statements of witnesses, documentary evidence, and the statement of the accused associated with appropriate evidence, the elements in the article as indicted by the public prosecutor, namely Article 158 in conjunction with Article 37 of Law Number 4 of 2009 concerning Mineral and Coal Mining, all of these elements have been fulfilled.